2016
DOI: 10.4236/ojce.2016.62008
|View full text |Cite
|
Sign up to set email alerts
|

Warm-Mix Asphalt and Pavement Sustainability: A Review

Abstract: Within the past two decades or so, the asphalt paving industry has responded positively to increasing global concerns over shrinking natural resource reserves and worsening environmental conditions through the development and deployment of warm-mix asphalt technologies. Such technologies make it possible to produce and place asphalt concrete at reduced temperatures compared to conventional hot-mix methods. Several studies have reported on the potential of warm-mix asphalt with regard to improved pavement perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…The idea behind WMA technology assumes that, with decreased production temperature, the physical and chemical properties of mix asphalt will be better or the same as in case of HMA [44,45].…”
Section: Effect Of Zeolite Addition On Wma Propertiesmentioning
confidence: 99%
“…The idea behind WMA technology assumes that, with decreased production temperature, the physical and chemical properties of mix asphalt will be better or the same as in case of HMA [44,45].…”
Section: Effect Of Zeolite Addition On Wma Propertiesmentioning
confidence: 99%
“…The use of WMA leads to a reduction in mixing and compaction temperatures of about 20-40 • C, if compared to the traditional HMA [18] and the addition of zeolites has been shown to further decrease the temperature [20]. As the required heat is reduced, plant and site emissions are lowered [21]. Life cycle assessment (LCA) studies have shown that a reduction of processing temperature is associated with a reduction of air pollution, smog production, and fossil fuel depletion [22]; on the other hand, the production of required additives may counteract the reduced environmental impact [7,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…This places elevated responsibility on industry professionals, to indulge in sustainable construction practices, in order to ensure that the activities of today's generation would not compromise and be detrimental to the ability of tomorrow's generation to prosper unhinged. It is reported that in the United States (U.S) alone, over 320 million tons or raw materials are used in the construction, rehabilitation and maintenance operations of the nation's road infrastructure network; project annual costs of over $150 billion [1].…”
Section: Introductionmentioning
confidence: 99%